Effects of Hereditary and Acquired Risk Factors of Venous Thrombosis on a Thrombin Generation-Based APC Resistance Test - Curvers, Joyce; Thomassen, M. Christella L. G. D.; Rimmer, Janet; Hamulyak, Karly; van der Meer, Jan; Tans, Guido; Preston, F. Eric; Rosing, Jan (Thrombosis and Haemostasis, 2002)
Several hereditary and acquired risk factors for venous thromboembolism (VTE) are associated with impaired down-regulation of thrombin formation via the protein C pathway. To identify individuals at risk, functional tests are needed that estimate the risk to develop venous thrombosis.We determined the effects of hereditary and acquired risk factors of venous thrombosis on an APC resistance test that quantifies the influence of APC on the time integral of thrombin formation (the endogenous thrombin potential, ETP) initiated in plasma via the extrinsic coagulation pathway. APC sensitivity ratios (APCsr) were determined in plasma from carriers of factor VLeiden (n = 56) or prothrombin G20210A (n = 18), of individuals deficient in antithrombin (n = 9), protein C (n = 7) or protein S (n = 14) and of women exposed to acquired risk factors such as hormone replacement therapy (n = 49), oral contraceptive use (n = 126) or pregnancy (n = 35). We also analysed combinations of risk factors (n = 60).The thrombin generation-based APC resistance test was sensitive for the factor VLeiden and prothrombin G20210A mutation, to protein S deficiency, hormone replacement therapy, oral contraceptive use and pregnancy. The assay was not influenced by antithrombin-or protein C deficiency. The presence of more than one risk factor of venous thrombosis resulted in more pronounced APC resistance. The APCsr of individuals with a single or combined risk factors of VTE correlated well with reported risk increases.The thrombin generation-based APC resistance test identifies individuals at risk for venous thrombosis due to acquired risk factors and/or hereditary thrombophilic disorders that affect the protein C pathway.
Keywords: Hereditary APC resistance; acquired APC resistance; thrombin generation-based test